Burundi : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The strategy underlying the Arusha agreement envisaged a three-year transition period, involving further national reconciliation steps, implementation of lasting power-sharing arrangements, and initiation of national reconstruction. To overcome poverty, Burundi should diversify its economy and establish new sources of economic growth. The increasing regional integration will also help to accelerate economic growth. The parallel market in Burundi is still sizable, and the exchange rate differential remains a source of financial distortion. The statistical data of economic indices of Burundi are presented in this paper.